Binder-free Fe2N nanoparticles on carbon textile with high power density as novel anode for high-performance flexible lithium ion batteries. (January 2015) - Balogun, Muhammad-Sadeeq; Yu, Minghao; Huang, Yongchao; Li, Cheng; Fang, Pingping; Liu, Yi; Lu, Xihong; Tong, Yexiang
Abstract: For the fabrication of flexible full lithium ion batteries (FLIBs), suitable anode material is highly demanded. Iron nitrides hold great promise as anode material for lithium ion batteries (LIBs) due to their large specific capacity and high electrical conductivity. However, their poor electrochemical stability severely limits their application as electrode material for LIBs. In this article, we synthesize binder-free Fe2 N nanoparticles (Fe2 N NPs) as high performance free-standing anode for LIBs. When tested in a half-cell, the binder-free Fe2 N NPs delivered a high reversible capacity of 900 mAh/g. At high current density of 6000 mA/g, the binder-free Fe2 N NPs exhibits excellent cyclic stability with 76% capacity retention after 300 cycles. We also demonstrated high power and energy density FLIB based on Fe2 N NPs anode and LiCoO2 cathode for the first time. The Fe2 N//LiCoO2 FLIB device shows attractive electrochemical performance and high flexibility. More importantly, Fe2 N//LiCoO2 FLIB device achieved a high power density of 3200 W/kg and a high energy density of 688 Wh/kg. These values are substantially enhanced compared to most of the reported LIB devices. This work constitutes the first demonstration of using Fe2 N NPs as high performance anode, which could potentially improve the performance of energy storage devices. Graphical abstract: Highlights: Fe2 N nanoparticles anode were synthesized through hydrothermal method and annealing. The Fe2 N nanoparticles exhibit excellent cyclic stability and rate capability. Flexible lithium ion battery device based on Fe2 N anode was designed. The flexible device exhibits high power and energy density.